Progression in multi-omics and immunological research on host-parasite interactions: Transcriptomics, proteomics, genomics, metabolomics, and immune responses - Lakshay Virmani; Aman Juyal (Recent Trends in Infectious Diseases, 2025)
The interaction occuring between hosts and parasites is a quick and multi step-complex biological process that tries to influence disease outcomes. In recent years, multi-omics approaches, such as transcriptomics, proteomics, genomics, metabolomics, and immunological studies, have gathered substantial eye in dissecting these interactions at a microscopic level. These techniques enable a vast understanding of the molecular structures involved in parasitic infections and host defense mechanisms. This article reviews the advancements in these multi-omics technologies and explains how they contribute to the elaboration of the host-parasite interaction. We show recent studies that connects these approaches and gives us a sight to look at their implications for developing novel therapeutic strategies, diagnostics, and vaccines. Moreover the plasmodium strain is taken into account with respect to its vivax category and its impact in different domains which leads to various anomalies in different interaction systems and its dependence on immune responses. The article review also talks about the mechanistic approaches with the host parasite relations and the deleterious effects of the strain. This inspection emphasizes important discoveries from multi -dimensional studies, such as identifying the expression of genes, only the process of changing the host's metabolism and modification. epigenetic between hosts and parasites By integrating many methods of data, paving the way for the development of antibiotic treatment, target and vaccine.
Keywords: Host-parasite interaction; Immune response; Multi- omics approaches; Plasmodium vivax; therapeutic strategies